Zero-pressure balloons trajectory prediction: Duster flight simulations. Issue 8 (15th October 2020) - Liuzzi, Vito; Della Corte, Vincenzo; Rotundi, Alessandra; Ivanovski, StavroL.; Dionnet, Zelia; Brunetto, Rosario; Inno, Laura
Abstract: DUSTER (Dust from the Upper Stratosphere Tracking Experiment and Retrieval) is a balloon-born instrument designed to collect dust particles with sizes less than 30 µm in the upper stratosphere (30 – 40 km), to be analysed in laboratory. In support to the DUSTER flight campaigns, it is crucial to predict the balloon trajectories according to atmospheric circulation and to estimate the landing. For a feasibility study of an Antarctic flight campaign we predict the DUSTER trajectory with a statistical approach, considering safety issues and the pivotal instrument recovery, to retrieve the collected samples. To this aim, we used the NOAA (National Oceanic and Atmospheric Administration) meteorological data and the HYSPLIT software (HYbrid Single Particle Lagrangian Integrated Trajectory). The Antarctic Polar Vortex, every year in the period December – January, generates a counter clockwise circulation (averaged wind speeds around 36 m/s from 29 to 35 km of altitudes). We evaluated the best launch opportunity windows for DUSTER to take advantage of the Polar Vortex starting from historical data. The NOAA meteorological data (Global reanalysis of atmospheric data – GFS Analysis and Forecasts products of the National Centers for Environmental Predictions - NCEP) from 1994 to 2015 allowed us to select the period after the 10th of January as the launch window maximizing the DUSTER time of flight. We used HYSPLIT program to project the balloon simulated trajectories on ground, providing critical information for the recovery operations. Successively, with the aim of becoming autonomous within the DUSTER team, i.e. taking care of the complete procedure to realize a DUSTER flight campaign, we developed a dedicated software, the DUSTER Flight Simulation Predictor (DFSP) that considers the ascent, floating and descent phases and the meteorological conditions. DFSP considers the balloon dynamics, the heat flow transfer between the balloon and the atmosphere, and the lifting variable gas mass to simulate the complete flight. We are now able to obtain balloon trajectory simulations with a flight time up to 240 h, starting and ending in any Earth geographical position. In the following paper, a comparison between real DUSTER flight data in 2009 and simulated DFSP data will be shown.